Viral anti-cancer therapy - Błażejewska, Paulina; Goździcka-Józefiak, Anna (Contemporary Oncology/Współczesna Onkologia, 2005)
Poor effectiveness of the conventional methods in treating cancer diseases has become one of the causes of searching for alternative ways of therapy. Extensive genetic, biological and biotechnological research has made it possible to understand better the mechanisms which control the cell cycle and identification of the factors involved in cancerogenesis. What is more, understanding the viral nature and viral infection mechanisms has created a scientific basis to develop new methods of the anticancer therapy by means of using viruses. Thanks to natural tropism of viruses to specific tissues and organ cells and the possibility of inserting a desirable genetic modification to the viral genome we can use viruses as anticancer factors. Virotherapy is safe if highly specified viruses in respect to structurally and functionally alternated cancer cells are applied and if they are strengthened by means of genetic modifications. It is crucial to modify the virus in such a way so that it could evoke lytic of a cell after having reached it. Viral vectors may be carriers for factors (for example proteins and prodrugs) involved in cell death, and they may induce a specific anticancer resistance and increase cancer cells sensitivity to chemotherapeutics. Vectors are created mainly on the basis of adenoviruses, herpes viruses, rabdoviruses and reoviruses.